Retrospective Evaluation of Acute Kidney Injury After Zoledronic Acid Administration to Dogs With Malignant Osteolysis - Vidal, Sarah A.; Skorupski, Katherine A.; Willcox, Jennifer L.; Palm, Carrie A.; Burton, Jenna H. (Frontiers in Veterinary Science, 2021)
Zoledronic acid (ZOL) is an intravenous bisphosphonate indicated for the use of hypercalcemia of malignancy and management of bony metastases. Its therapeutic effect lies in the targeting of malignant osteoclasts; however, administration can be associated with renal toxicity. The objective of this retrospective study was to evaluate the frequency and severity of acute kidney injury (AKI) following ZOL administration in a cohort of cancer-bearing dogs. A pharmacy search was conducted to identify dogs that received a dose of ZOL between June 2016 and July 2019. Inclusion criteria included baseline and post-treatment chemistry panels. Medical records were reviewed to obtain clinical data including signalment, dose, dosage, number of treatments administered, and changes in renal function. Forty-four dogs met inclusion criteria. Median number of doses administered was three (interquartile range (IQR), 2 - 5). The median highest creatinine value occurred after a median of one dose (IQR, 1-2 doses) as compared to the median highest value of blood urea nitrogen, phosphorus, and potassium which occurred after a median of two doses (IQR, 1-3). Six (13.6%) dogs developed an AKI and one dog (2.3%) had progression of an existing azotemia after treatment with ZOL was initiated. Two dogs (4.5%) had ZOL treatment discontinued secondary to development of azotemia. Use of concurrent administration of non-steroidal anti-inflammatory drugs or anesthesia did not significantly increase the risk of AKI in this cohort of dogs. Acute kidney injury is observed infrequently in cancer-bearing dogs treated with ZOL and is generally mild to moderate in severity; discontinuation of ZOL due to AKI is uncommon.